Landbruget i Japan følger trop: Vil være net-zero og 25 procent økologisk inden 2050. - Christensen, A. (Tidsskrift for Landøkonomi, 2024)
Landbruget i Japan følger trop: Vil være net-zero og 25 procent økologisk inden 2050.